Association of MC1R variation and plumage color diversity of Nigerian domestic pigeon (Columba livia domestica) (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: Domestic pigeons (Columba livia domestica) have diverse plumage pigmentations. Melanocortin 1 receptor (MC1R) gene variation has been correlated with color traits. The association between MC1R and plumage coloration in African domestic pigeons is yet to be investigated. Materials and Methods: Herein, we report the relationships between single nucleotide polymorphisms (SNPs) in MC1R and plumage of 35 domestic pigeons from Nigeria with 4 different plumage phenotypes plus 37 published MC1R sequences from France (n = 14) and Russia (n = 11). Results: We obtained 14 SNP sites among 72 individuals. Missense mutations C206T (Ser69Leu) and G253A (Val85Met) were observed in 16 and 8 Nigerian pigeons, respectively. The chi-squared test (p < 0.05) for C206T, G253A, and A520G has the advantage of homozygous genotypes CC, GG, and AA, respectively. The association of C206T loci showed the advantage of CC genotype in ash-red, spread, and white pigeons, and TT in blue-bar, spread, and white feather pigeons. For G253A and A520G loci, GG and AA were dominant in all plumages except for genotype AA in G253A, which was prominent in ash-red, spread, and white plumages. The three SNPs were assigned to seven haplotypes. The median-joining network revealed 20 haplotypes, including 5 in Nigeria and 2 shared. Conclusion: This study provides an insight into the association of MC1R variation and plumage diversity in Nigerian domestic pigeons. However, due to the limitation of the current data, we could not make further conclusions; this necessitates the need for more genomics studies on Nigerian pigeons.J. Adv. Vet. Anim. Res., 9(3): 369–373, September 2022http://doi.org/10.5455/javar.2022.i604